Existentialism In Shakespeare’S Hamlet: Exploring existentialism in Shakespeare's Hamlet (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Few philosophical movements have aroused as much interestas existentialism. The dictionary Merriam-Webster Online defines existentialismas a “philosophical movement…centering on analysis of individual existence inan unfathomable universe and the plight of the individual who must assumeultimate responsibility for acts of free will.” The term ‘existentialism’ hasmostly been associated with a movement that grew out of the war timeintellectual atmosphere in Paris and spread through fiction and art as much asphilosophy. Its impact has been felt beyond the academy, in literature, inpolitics and thought. William Shakespeare is the most notable and influentialauthor of the Elizabethan period of English literature. Shakespeare’scharacters and the way he presents them indicate a significant difference fromhis contemporaries. Some of the Shakespeare’s major characters, both in theearly and the later plays, exhibit modes of feeling and perception that bringtheir motivations in consonance with the philosophy of existentialism. Thepresent paper studies the existentialism in Shakespeare’s play Hamlet. Thedelight in Shakespeare springs from the dual vision of human littleness and ofhuman greatness from the diverse threads of weakness and nobility which areinscrutably woven together in the mystery of human existence.